Structural and functional characterization of ModA and TupA proteins belonging to the molybdate and tungstate transport system from desulfovibrio alaskensis G20 - Cordeiro, Raquel Sofia Correia (2015)
Fundação para a Ciência e Tecnologia - EXPL/BBB-BEP/0274/2012